The role of religious leaders on digital piracy attitude and intention. (September 2016) - Casidy, Riza; Phau, Ian; Lwin, Michael
Abstract: This study examines the role of religious leaders and individual's religiousness in affecting attitude towards digital piracy and behavior intention. The data analysis of 400 usable responses from a religious organisations provided several significant relationships. Attitude towards digital piracy and subjective norms has a negative relationship with digital piracy intention. There are also significant differences between highly religious and less religious respondents in terms of their attitude towards digital piracy, motivation to comply with their religious leaders, and intention to engage in digital piracy behavior. Highlights: This study is one of the pioneering study that examines the role of religious leaders and individual religiousness in affecting people's digital piracy attitude and behavior. In particular, it investigates the effects of one's religiousness on key elements of the Theory of Planned Behavior, including attitude towards the behavior, motivation to comply with specific referents, and behavioral intention.